2009
DOI: 10.1111/j.1467-8489.2009.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of credence and health information in determining US consumers’ willingness‐to‐pay for grass‐finished beef

Abstract: Consumer demand for forage-or grass-finished beef is rapidly emerging in the US. This research uses data elicited from consumer surveys and experimental auctions to provide insight on product attributes (taste/flavour, credence and nutritional characteristics) and socio-demographic factors that are most important in determining US consumers' preferences and willingness to pay premiums for grass-finished versus grain-finished beef. Information related to beef production processes increased the probability consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 24 publications
5
50
2
Order By: Relevance
“…"AGE" was negative and significant for New York steak and ground beef at both stages (negative effect of 4.7 percent to 7.8 percent for an additional 10 years of age), indicating that younger adults were more willing to purchase and pay premiums for differentiated beef products. This result is consistent with previous studies on consumer preferences for grass-fed beef (Umberger et al, 2009), which demonstrate the reluctance of older adults to incorporate new foods into their diet (Pollak, 1970).…”
Section: Model Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…"AGE" was negative and significant for New York steak and ground beef at both stages (negative effect of 4.7 percent to 7.8 percent for an additional 10 years of age), indicating that younger adults were more willing to purchase and pay premiums for differentiated beef products. This result is consistent with previous studies on consumer preferences for grass-fed beef (Umberger et al, 2009), which demonstrate the reluctance of older adults to incorporate new foods into their diet (Pollak, 1970).…”
Section: Model Resultssupporting
confidence: 83%
“…A study by Lusk and Parker (2009) found that consumers preferred grass-fed beef over supplementing a primarily grain diet to improve Omega 6:3 ratios, and a study by Umberger, Boxall, and Lacy (2009) showed that health-related messages and nutritional-content labeling were important drivers of U.S. consumer WTP for grass-finished beef. Xue, Mainville, You, and Nayga (2010) and Chang, Xu, Warmann, Lone, Munzimi, and Opoku (2013) found that in addition to consumer beef consumption rates, experience with food-related diseases and nutrient and health knowledge significantly impact consumer WTP for local and grass-fed beef.…”
Section: Previous Literaturementioning
confidence: 99%
“…Consumers' interest in, and willingness to pay (WTP) for, products varies substantially with population demographics and product attributes (e.g. Dickinson and Bailey, 2005;Lusk et al, 2003;Umberger et al, 2009). Although previous studies showed consumers were willing to pay more for meat produced with reduced resource use and greenhouse gas (GHG) emissions (Blecher et al, 2007;Hurley et al, 2006;White and Brady, 2013), it is unknown whether this WTP would be sufficient to offset potential increases in operating costs associated with improving forage quality and nutrient use efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Rearing conditions may influence purchase behavior of consumers from different countries in different ways. As an example, in the United States of America, the consumer's demand for forage finished beef has increased (UMBERGER et al, 2009), leading to a potential market niche. However, lack or very low availability of WFP from ruminants observed in our research may be a consequence of a common perception about rearing conditions in Brazil.…”
Section: Product Availabilitymentioning
confidence: 99%